KOMPETENSI SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU PADA SMA NEGERI 1 KUALA BATEE KABUPATEN ACEH BARAT DAYA. - Afriadi, Nasir Usman, Niswanto. (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2016)
Abstract: Supervision competence of principalis one of the factors that affects the increase of teacher professionalism. This study was aimed at describing: (1) the competence of principal in preparing the academic supervision program to improve the professionalism of teachers, (2) the competenceof principal in implementing the academic supervision program to improve the professionalism of teachers, and (3) the competence of principal in following up the results of academic supervision to improve the professionalism of teachers. This research used descriptive method with qualitative approach. The tehniques of data collection were conducted through observation, interview, and documentation study. The subjects of the research were principal, vice-principal, teachers and school supervisors. The results showed that: (1) The principalof SMA Negeri 1 Kuala Batee Aceh Barat Daya district has demonstrated a good supervision competence, particularly in preparing the academic supervision programs for the teachers. It can be seen from supervision program that has been prepared by setting goals, objectives, and implementation procedures of supervision, but it was still less cooperation with the school supervisors.(2) ) The principalof SMA Negeri 1 Kuala Batee Aceh Barat Dayaregency has demonstrated a good supervision competence, particularly in implementing the academic supervision.It can be seen from the implementation of models, approaches, and techniques of supervisionhave been conducted,but the implementation of observation techniques have not been equipped with observation guide and (3) Supervision competence of the principal of SMA Negeri 1 Kuala Batee Aceh Barat Daya district particularly in following up the results of supervision was still less. It can be seen from the follow up of the supervision conducted by evaluating and providing feedback through individual talk with the teachers supervised, but the principal did not draw up an action plan for the next supervision.Keywords: Supervision Competence, Principal and Teacher Professionalism.Abstrak: Kompetensi supervisi kepala sekolah merupakan salah faktor yang mempengaruhi peningkatan profesionalisme guru. Penelitian ini bertujuan untuk mendeskripsikan: (1) kompetensi kepala sekolah dalam menyusun program supervisi akademik untuk meningkatkan profesionalisme guru, (2) kompetesi kepala sekolah dalam mengimplementasikan program supervisi akademik untuk meningkatkan profesionalisme guru, dan (3) kompetensi kepala sekolah dalam menindaklanjuti hasil supervisi akademik untuk meningkatkan profesionalisme guru. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data yang digunakan melalui observasi, wawancara, dan studi dokumentasi. Subjek penelitian adalah kepala sekolah, wakil kepala sekolah, guru, dan pengawas sekolah. Hasil penelitian menunjukkan bahwa: (1) Kepala SMA Negeri I Kuala Batee Kabupaten Aceh Barat Daya telah menunjukkan kompetensi supervisi yang baik, khususnya dalam menyusun program supervisi akademik terhadap guru. Hal ini dapat dilihat dari program supervisi yang telah disusun dengan menetapkan tujuan, sasaran, dan prosedur pelaksanaan supervisi, namun masih kurang kerja sama dengan pengawas sekolah. (2) Kepala SMA Negeri I Kuala Batee Kabupaten Aceh Barat Daya telah menunjukkan kompetensi supervisi yang baik, khususnya dalam mengimplementasikan program supervisi akademik. Hal ini dapat dilihat dari penerapan model, pendekatan, dan teknik supervisi yang dijalankan, namun dalam penerapan teknik observasi belum dilengkapi dengan pedoman observasi dan (3) Kompetensi supervisi kepala SMA Negeri I Kuala Batee Kabupaten Aceh Barat Daya khususnya dalam menindaklanjuti hasil supervisi masih kurang. Hal ini dapat dari tindak lanjut hasil supervisi dilakukan dengan mengevaluasi dan memberikan umpan balik melalui pembicaraan individual dengan guru yang disupervisi, namun kepala sekolah tidak menyusun rencana aksi supervisi berikutnya. Kata Kunci: Kompetensi Supervisi, Kepala Sekolah, dan Profesionalisme Guru.